On the Way of Discovering the Native Land - AVAGYAN, ARTSRUN (Bulletin of Yerevan University B: Philology, 2021)
The article presents Vahan Tekeyan’s diary “Caesarea”, which was written in 1913 and was first published in 1921 in the newspaper “People’s Voice – Zhamanak” in Constantinople. The Diary this time was published as a book in Istanbul in 2016. This work of V. Tekeyan is significant not only for the recognition of some fragments of his biography but also for revealing many aspects of the life of the Armenians in Caesarea.